Post-COVID wellness tourism: providing personalized health check packages through online-to-Offline services. Issue 24 (17th December 2022) - Huang, Yu-Ting; Tzong-Ru, Lee; Goh, Alexis P. I.; Kuo, Jehn-Hwa; Lin, Wen-Yu; Qiu, Si-Ting
ABSTRACT: This study proposed a new approach to wellness tourism through organizations' offering of wellness services as part of Online-to-Office (O2O) services to their employees. Targeted group data from 319 participants found medical professionalism, medical reports' accuracy, and privacy protection to influence their health check provider selection. Through certified medical advisement, R analysis, and filtering/sorting of 16523 sets of medical data, personalized health check packages for Generation COVID, Generation Y-Millennials, and Sandwich Generation were obtained. Together with medical services and wellness tourism providers, organizations could utilize these results to offer personalized wellness tourism packages to their employees accordingly, invoking a sense of Perceived Organizational Support (POS) among them. This proposed tripartite cooperation may offer a lifeline to all parties in this post-pandemic era.